COPYRIGHT PROTECTION OF SONG AND MUSIC USED COMMERCIALLY BY CAFE REGARDING ROYALTY PAYMENT (A Comparative Study of Indonesian and Singaporean Laws) - Qathrunnada, Qathrunnada; Sanusi, Sanusi (Student Journal of International Law, 2022)
This paper is a comparative study that analyzes policies regarding the payment of song royalties in Indonesia and Singapore through the Indonesian Copyright Law 2014 and the Singapore Copyright Law 2021. The paper used normative legal research that focuses on written legal norms, with main data from international laws, Indonesian and Singaporean laws, and other related government regulations. The results show that there are various regulatory similarities between Indonesia and Singapore regarding copyright because the two countries ratified the same international conventions, but of course there are differences. Lessons that can be learned from Singapore in terms of managing song royalties is managed by one Collective Management Organization (CMO) and assisted by digital technology system called Soundsys in collecting and distributing royalties.